Endocrine changes in cerebrospinal fluid, pituitary effluent, and peripheral plasma of anesthetized ponies - Luna, Stélio Pacca Loureiro [UNESP]; Taylor, Polly M.; Bloomfield, Malcolm (My University, 1997)
Objective - To investigate the effects of inhalation and total IV anesthesia on pituitary-adrenal activity in ponies. Animals - 9 healthy ponies: 5 geldings and 4 mares. Procedure - Catheters were placed in the cavernous sinus below the pituitary gland and in the subarachnoid space via the lumbosacral space. After 72 hours, administration of acepromazine was followed by induction of anesthesia with thiopentone and maintenance with halothane (halothane protocol), or for the IV protocol, anesthesia induction with detomidine and ketamine was followed by maintenance with IV infusion of a detomidine-ketamine-guaifenesin combination. Arterial blood pressure and gas tensions were measured throughout anesthesia. Peptide and catecholamine concentrations were measured in pituitary effluent, peripheral plasma, and CSF. Peripheral plasma cortisol, glucose, and lactate concentrations also were measured. Results - Intravenous anesthesia caused less cardiorespiratory depression than did halothane. ACTH, metenkephalin, arginine vasopressin, and norepinephrine pituitary effluent and peripheral plasma concentrations were higher during halothane anesthesia, with little change during intravenous anesthesia. Pituitary effluent plasma β-endorphin and peripheral plasma cortisol concentrations increased during halothane anesthesia only. Dynorphin concentrations did not change in either group. Hyperglycemia developed during intravenous anesthesia only Minimal changes occurred in CSF hormonal concentrations during anesthesia. Conclusion - The pituitary gland has a major role in maintaining circulating peptides during anesthesia. Compared with halothane, IV anesthesia appeared to suppress pituitary secretion.
Keywords: animal experiment; cerebrospinal fluid analysis; female; horse; hypophysis function; intravenous anesthesia; male; nonhuman; veterinary medicine; Adrenocorticotropic Hormone; Anesthesia, Inhalation; Anesthesia, Intravenous; Animals; Arginine Vasopressin; beta-Endorphin; Female; Halothane; Horses; Hydrocortisone; Male; Pituitary Gland; Animalia; Equus caballus